The R&D tax credit : issues in tax policy and industrial innovation - Brown, Kenneth M.; American Enterprise Institute for Public Policy Research (Washington : American Enterprise Institute for Public Policy Research, 1984)
Incentives for research and development are essential if the United States is to regain and maintain technological and industrial leadership in global markets. This publication brings the issue of tax incentives before the public most effectively
"A conference sponsored by the American Enterprise Institute for Public Policy Research"--Cover.
asm 23/01/2019
Loans
Keywords: Research and development tax credit; Research, Industrial